Software GeoGebra: As an Assistance to the Guided Inquiry Model in Improving Students' Numeracy Skills - Made Agus Adi Setyawan; I Made Citra Wibawa (Universitas Pendidikan Ganesha, 2023)
Students' numeracy skills are still low because mathematics is presented abstractly. Moreover, teachers are less attractive in packaging the learning models and media used, and the application of learning is still conventional and less interactive. The aim of this research is to testThe influence of the guided inquiry model assisted by GeoGebra software on the numeracy abilities of class IV students. The research method is quantitative with a quasi-experimental design with a Non-Equivalent Control Group Design. The study population was 76 students, with sample determination using saturated sampling techniques, 38 students as the control class and 38 students in the experimental class who would be given learning using the guided inquiry model assisted by GeoGebra software. Data was collected using a test method in the form of descriptions obtained after 5 treatments. The instrument uses a set of tests in the form of descriptions. Data analysis techniques use descriptive statistics and inferential statistics (t-test). The results of hypothesis testing showed that the average score of the experimental group was greater than the average score gain of the control group. Based on the results of the data analysis, it can be concluded that there is a significant influenceguided inquiry model assisted by GeoGebra software on the numeracy abilities of class IV students. So, learning activities using GeoGebra software can help to visualize mathematical concepts which can improve students' numeracy skills.